Evaluasi Farmakologis dan Toksikologis Ekstrak Etanol Daun Kratom (Mitragyna speciosa) sebagai Kandidat Analgesik Selektif COX-2 dengan Aktivitas Stimulan Sistem Saraf Pusat dan Profil Keamanan Akut pada Mencit - Presetya, Fajar; Bafadal, Mentarry; Muhlisa Mus, Nurul; Ramdhani Sahar, Fikri; Onny Ziasti Fricillia; Pryenalvend Khisanta Piter; Gayuk Kalih Prasesti; Noviani, Lusy (Jurnal Sains dan Kesehatan, 2025)
Kratom (Mitragyna speciosa) is a tropical plant containing various bioactive alkaloids such as mitragynine, 7-hydroxymitragynine, speciogynine, and paynantheine, known for their analgesic and stimulant activities. Unlike classical opioids, kratom has been reported to possess a lower risk of dependence and may act through inhibition of non-opioid inflammatory pathways such as cyclooxygenase (COX) and Toll-like receptor 4 (TLR4). This study aimed to evaluate the inhibitory activity of kratom leaf ethanol extract on COX-1 and COX-2 enzymes, assess its acute toxicity in mice, and determine its central nervous system (CNS) stimulant potential through the natatory exhaust test. The 96% ethanol extract of kratom leaves was tested for COX-1 and COX-2 inhibition using the TMPD assay method. Acute toxicity was evaluated following OECD guideline 423 at doses ranging from 5 to 2000 mg/kg BW in female mice. The stimulant activity test was conducted using the natatory exhaust method in male mice at doses of 50, 100, and 150 mg/kg BW. Statistical analysis was performed using ANOVA followed by Tukey’s test with a 95% confidence level. The extract exhibited 74.38% inhibition of COX-2 and 2.47% inhibition of COX-1 at a concentration of 1000 ppm, yielding a selectivity ratio of 30:1. Acute toxicity testing showed an LD₅₀ > 2000 mg/kg BW, categorized as mildly toxic, with no significant organic alterations. CNS stimulant activity increased up to 280% at a dose of 150 mg/kg BW compared to the negative control. The ethanol extract of kratom leaves demonstrates potential as a selective COX-2 analgesic with CNS stimulant effects and a favorable acute safety profile. Its pharmacological mechanism likely involves COX-2 inhibition and enhanced dopaminergic transmission.